Tingkat Pengetahuan tentang Pandemi Covid-19 dengan Kepatuhan Memakai Masker - Tria Eni Rafika Devi; Rizky Dwiyanti Yunita (Akademi Kesehatan Rustida, 2021)
This study aims to analyze the relationship between the level of knowledge about the covid-19 pandemic and compliance with wearing masks in residents of RT 02 RW 01 Sumberberas Muncar Village Banyuwangi in 2020. This study is a quantitative study with a cross- sectional approach, data analysis using the Kendall's tau correlation test. The population in this study was 40 respondents. The research sample was taken with a total sample of 40 respondents. The independent variable in this study is the level of community knowledge and the dependent variable is compliance with using masks. Based on the results of the study, there were 25 respondents who had less knowledge and did not comply, there were no respondents who had less knowledge and were obedient, there were 5 respondents who had good knowledge and were not obedient and 10 respondents who had good knowledge and were obedient. . The results of the Kendall's Tau correlation test output obtained a significance value between knowledge and compliance of 0.000 <0.05. So it can be concluded that there is a significant relationship between knowledge and compliance.